Nano-curcumin influences blue light photodynamic therapy for restraining glioblastoma stem cells growth. Issue 97 (5th October 2016) - Dev, A.; Srivastava, A. K.; Choudhury, S. Roy; Karmakar, S.
Abstract : Nano-curcumin based blue light photodynamic therapy has therapeutic potential in the arsenal of glioblastoma cancer stem cells recurrence. Abstract : Very low doses of curcumin loaded BSA nanoparticles, following blue light mediated photodynamic therapy, provide improved cytotoxicity against glioblastoma stem cells.